Optimalisasi Pemanfaatan Infrastruktur Fiber: Analisis Strategis PT Telkom Infrastruktur Indonesia Menggunakan SWOT dan QSPM - Setiawan, As'at Rahmat; Sutjipto, Mohammad Riza (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2026)
Business transformation has become a strategic necessity for telecommunications companies operating in increasingly competitive and dynamic environments. PT Telkom Infrastruktur Indonesia (PT TIF), established under Telkom Group’s 5 Bold Moves initiative, functions as an InfraCo entity responsible for managing and commercializing fiber network infrastructure. However, the company faces challenges related to low infrastructure asset utilization and limited external revenue generation beyond the Telkom Group ecosystem. This study aims to formulate appropriate business strategies to optimize asset utilization and improve competitiveness. A descriptive qualitative approach was employed. Data were collected through semi-structured interviews with five key informants representing PT TIF management, industry associations, and Internet Service Provider (ISP) companies, supported by direct observation and analysis of company documents and industry reports. The study utilized PESTEL Analysis, Porter’s Five Forces, SWOT Analysis, Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, IE Matrix, TOWS Matrix, and Quantitative Strategic Planning Matrix (QSPM). Results indicate that PT TIF possesses significant strengths, including extensive nationwide infrastructure coverage and strong brand support from the Telkom Group, but faces weaknesses in operational agility, marketing capability, and capital expenditure limitations. QSPM analysis identifies Network Sharing Expansion as the priority strategy to improve infrastructure utilization, increase external revenue.